Achieving Access to External Finance Among Indonesian Entrepreneurs Through Financial Literacy, Financial Inclusion, Availability of Collateral, and Government Policy: A Study on Large Industrial Entrepreneurs in West Java - Fachrurazi; Arief Yanto Rukmana; Sutrisno; Efendi (Eastasouth Institute, 2023)
Access to external finance is crucial for the success and growth of entrepreneurs, especially in developing countries like Indonesia. This study examines the relationship between financial literacy, financial inclusion, collateral availability, government policy, and the achievement of external finance access among large-scale industrial entrepreneurs in West Java. Using a structural equation model with Smart PLS, data was collected from a sample of 200 entrepreneurs in West Java. The findings show that financial literacy has a significant positive influence on the achievement of external finance access, followed by financial inclusion, collateral availability, and government policy. These results indicate that policymakers and financial institutions should focus on improving financial literacy and increasing financial inclusion to enhance external finance access for entrepreneurs. Additionally, entrepreneurs should strive to improve their financial literacy to increase their opportunities for accessing external finance.